Framing Analysis of the Mayor's Image in the News of Eri Cahyadi's Participation with the Vespa Community on the RRI.Co.Id News Portal - Adha, Yusi Kesuma \; Zulaikha, Zulaikha; Prasetyo, Iwan Joko; Maella, Nurannafi Farni Syam (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
This study analyzes the framing of the image of Mayor Eri Cahyadi in the news coverage of the summer event ‘Surabaya Bervespa’ published on the RRI.co.id news portal. Using Pan and Kosicki's four structural device models, syntactic, script, thematic, and rhetorical structures. this study explores how the news forms the image of the Mayor through various framing elements. The results show that the news effectively forms the image of Eri Cahyadi as a leader who supports the Vespa community and promotes tourism in Kota Lama. The syntactic structure places the Mayor in the center of attention, while the script structure provides comprehensive information about his role in the event. The main theme of the news highlights the Mayor’s support for the community and tourism, while the rhetorical structure uses word choice, idioms, and images to strengthen the positive image. This study's novelty lies in framing analysis to reveal how news forms public perceptions of local leaders through integrated and layered framing. This study provides insight into political communication strategies and the influence of news framing in shaping a leader's public image.